User Authenticating and Necessary Data Processing without Private Key in Cloud Computing - K.Ravi sekhar, Dr.K.Subrahmanyam (International Journal of Advanced Science and Technology, 2020)
Providing security to data is key to the success of storing in servers. Cloud computing has capable of storing infinity data in its servers. So coming to authentications a maximum number of verification problems facing to secure our data and identification problems. To satisfy an authentication and verification progress third party’s (TPA) servicing user-friendly to owners of data besides users fetching progress. So for that, we proposed the third party’s authentication to owners of data and users. We proposed a mechanism called fetching data without keys. The authenticated owners can able to store the data in the cloud and authenticated users can fetch the data. Over that TPA verifies the owners of data and users, so this is the key challenge. Owners and users must be verified through different verification schemes called one-time password, biometric authentication and verification progress by TPA. Keywords: Cloud computing, TPA, One time password, Biometric authentication, Verification.